Erasmus+ international staff mobility programme ignites intercultural exchanges and global collaboration - Abdullah Adnan, Mohamed; Nik Aloesnita, Nik Mohd Alwi; Mohd Azmir, Mohd Azhari (2023)
The Center for Modern Languages (CML) Universiti Malaysia Pahang (UMP) recently hosted a stimulating week of international collaboration under the esteemed Erasmus+ International Staff Mobility Programme funding. The mobility programme is funded under the framework of Erasmus+ International Credit Mobility (ICM) KA107 Project. At UMP, the Center for International Relations (CIR) is responsible for coordinating with potential higher education institutions from Erasmus+ Programme Countries in applying for the ICM grant. UMP has signed a few inter-institutional agreements worldwide for the ICM KA107 project.